Ethnoeducation and differentiated basic education for indigenous peoples and quilombola communities in Brazil: a challenge for the promotion of ethnodevelopment - Moraes, Nelson Russo de [UNESP]; Souza, Fernando da Cruz [UNESP] (Univ Federal Santa Maria, 2022)
The dialogue in the field of education is undoubtedly one of the most heated in the academic and scientific world, given its interdisciplinary and increasingly complex perspectives, especially given its inclusion challenges even in societies with great cultural diversity. The production and reproduction of knowledge within the historical, anthropological realities and resulting from the rights and public policies aimed at indigenous peoples (original peoples of Brazil) and quilombolas (traditional brazilian communities) is a challenging field for the academy, especially when considering at its core that there will always be social education and school education. This communication produces articulation between three sets of research on ethnoeducation as a subsidy for differentiated school education for indigenous and quilombolas, carried out in two public universities (UNESP and UFT) under the articulation of the research group GEDGS (Group of Studies in Democracy and Management Social), between 2015 and 2021. The first set brings complementary research funded by UNESP and CNPq on the investment of international social organizations in educational projects in traditional Amazonian communities; the second set articulates the results of two researches on public policies for indigenous education and, finally, a last research brings an important perception about orality (including intergenerational) as a vehicle for the production of school knowledge. The research, whose complete documents have already been published, converge to substantial aspects of the quality of differentiated education for indigenous people and quilombolas, which permeates ethnoeducation, in turn based on the concept of ethnodevelopment.
Keywords: Ethnoeducation; Indigenous school education; Public education policies